Board Diversity and Corporate Risk: Evidence from the Indonesian Manufacturing Companies Listed in the IDX in 2016-2019 - Fransisca Shania; Pamela Andriani (iBuss Management, 2021)
Recently, board diversity has become an essential part of the modern business environment. Its awareness rises since it affects how the board carries out its duties, the board's efficacy, and the risk-taking behavior, leading to companies' outcomes and value. Regardless of its prominence, limited studies analyzed the relationship between board diversity and corporate risk. However, none of them use Indonesian firms as a subject of observation. Therefore, the researchers conducted the study to know the impact of board diversity, precisely, the Board of Commissioner and corporate risk with the diversity of gender, age, nationality, education, and tenure as independent variables. The dependent variable, corporate risk, was operationalized using the standard deviation of annualized stock returns. Board size, market to book ratio, tangibility, leverage, and profitability were used as control variables. This study focused on Indonesia's manufacturing companies listed in the IDX during 2016-2019, with 300 sample data collected from 75 companies. The data gathered passed the purposive sampling criteria and were further analyzed using multiple linear regression. Based on statistical processes, nationality diversity, tangibility, leverage, and profitability significantly affect corporate risk. Inversely, diversity of gender, age, education, tenure, the board size, and market-to-book ratio do not significantly affect corporate risk.Keywords:Board Diversity, Gender Diversity, Age diversity, Nationality Diversity, Education Diversity, Tenure Diversity, Corporate Risk.